ChemInform Abstract: Copper‐Mediated One‐Pot Synthesis of Trifluorostyrene Derivatives from Tetrafluoroethylene and Arylboronate. Issue 6 (21st January 2016) - Kikushima, Kotaro; Sakaguchi, Hironobu; Saijo, Hiroki; Ohashi, Masato; Ogoshi, Sensuke
Abstract: A copper‐mediated synthesis of trifluorostyrene derivatives is developed.